Bankruptcy and Insider Trading: Differences Between Exchange‐Listed and OTC Firms - GOSNELL, THOMAS; KEOWN, ARTHUR J.; PINKERTON, JOHN M. (Journal of Finance, 1992)
ABSTRACT Over the two‐year period prior to the bankruptcy announcement, insider trading is significantly greater for OTC bankrupt firms, but not for exchange‐listed firms, than for an industry‐size matched sample of nonbankrupt firms. In addition, the level of insider selling increases over the final five months leading to the first public announcement of OTC firms. Finally, firms displaying the most negative price reaction over the announcement period are found to have a significantly larger proportion of insider selling than other firms.